Exploring Indonesian Students’ Views on Solar Panels and Fossil Fuels: Education for Sustainable Development Perspective - Rusmana, Ai Nurlaelasari; Dhitareka, Putra Habib; Aini, Rahmi Qurota; Sya’bandari, Yustika (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Understanding how young people perceive renewable and non-renewable energy sources is essential for aligning education with Sustainable Development Goals (SDGs). This study explores the perspectives of 748 Indonesian high school students on solar panel versus fossil fuels through an open-ended question. Different from previous studies, this work uses semantic network analysis to map the conceptual connections in students’ understanding, which provides us a structural perspective on students’ perceptions. Using semantic network analysis with NetMiner, 748 Indonesian students’ responses were categorized into five ideas: Fossil fuels formation (G1), Solar panel role in sustainability (G2), Practical benefits of solar panels (G3), Non-renewable resource concern (G4), and Unsustainable fossil fuels use (G5). The findings indicate that students have a basic understanding of environmental and resource-related issues. Most responses remain surface level with limited demonstration of critical thinking. Furthermore, students’ ideas primarily address the environmental and economic pillars of Education for Sustainable Development (ESD) while the social pillar is rarely discussed. These results highlight the need to improve ESD practices in Indonesia by explicitly integrating social dimensions into sustainability education. Empowering students to consider who is affected by sustainability decisions, and how they can contribute to fairer, more inclusive solutions can help to increase not only environmental awareness but also foster civic responsibility and empathy.